Contribution of Competency Mapping and Employees Effectiveness of Private Banks in Urban Jhansi: Impact of Technological Advancement on HR Management in Private Banks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Technological advancement brings many modifications that can impact the operation of the human resource and make it easier and quicker than ever. The management of human resources has always played a very important role in enhancing and improving organisational efficiency. HR is an organization's most precious assets that are never deprived. Building people to create a business enterprise is an acknowledged fact. Innovative ways of carrying out HR work are encouraged by the use of Information and Communication Technology (ICT). E-Personel leadership can be the most important driving force for organisational success to be achieved. EHRM has created few buzzwords such as automation, accountability, empowerment, paperless office with least human intervention, a truth that was once supposed to be the panacea for all workplace ills.